308-nm excimer lamp for the treatment of alopecia areata: Clinical trial on 16 cases - Akiko Ohtsuki; Toshio Hasegawa; Etsuko Komiyama; Atsushi Takagi; Junko Kawasaki; Shigaku Ikeda (Wolters Kluwer Medknow Publications, 2013)
Background: Alopecia areata (AA) is considered as a T-cell mediated autoimmune disorder. The 308-nm excimer laser is thought to be capable of inducing T-cell apoptosis in vitro, suggesting that the 308-nm excimer lamp (not laser) might be effective for the treatment of AA. We examined the effectiveness of the 308-nm excimer lamp for treating AA. Materials and Methods: We treated 16 patients with single AA and multiple AA (MAA). The lesions were irradiated with a 308-nm excimer lamp at 2-week intervals. Results: Hair regrowth was observed in 14 patients. Among them, 10 patients showed more than 50% hair re-growth. Our results suggested that the 308-nm excimer lamp system is effective and safe for the treatment of single AA and MAA. Conclusion: Our results suggest that the 308-nm excimer lamp is a good therapeutic alternative without serious side effect for treating AA.